Internal Standards of Economic Entity: A Tool to Improve its Accounting System and the Way to Comply with the Requirements of Federal Law of the Russian Federation “On Accounting” Regarding Organizing and Exercising Internal Control - Kostina, Zinaida Aleksandrovna; Safronova, Galina Petrovna; Mashentseva, Galina Aleksandrovna (International Journal of Economics and Financial Issues, 2016)
Today far from every Russian organization has a full system of maintaining accounting records and making accounting statements as well as a system of internal control over legislative documents that comply with the contemporary requirements where more and more attention is paid to the issues of standardizing the procedure of maintaining accounting records. Today competent composition of accounting and control systems at the enterprise is an actual problem that stipulated the urgency and the goal of the research topic. The analysis of the system of regulatory documents allowed to determine the place of a new document for the Russian accountant in the area of regulating accounting – a standard of an economic entity. It also led to a univocal conclusion about the necessity to form two packages of documents regulating the practice of its accountancy at the enterprise. Firstly, like it used to be before, this is an accounting policy. Secondly, these are standards of an economic entity. The uncertainty of the problem related to practical implementation of the economic entity's obligation to organize and exercise internal control of the performed facts of the economic activity also predetermined the development and use of internal standards and standards related to organizing and exercising internal control by business entities as its solution. Keywords: organization and maintaining of accounting and exercising control, internal standards of the economic entity. JEL Classifications: M41, M10